Effect of lipid bilayer composition on membrane protein association - Pawar, Aiswarya B.; Prasanna, Xavier; Sengupta, Durba (Advances in Planar Lipid Bilayers and Liposomes, 2015)
Diverse cellular functions are supported by membrane protein assemblies associated with the cell membrane. Although considered to be protein-mediated, membrane components are now being recognized as critical in modulating and sometime dictating function. This chapter discusses the effect of the lipid bilayer, in particular its composition on membrane protein organization. Computational methods have been successful in quantifying transmembrane protein association and general features of dimerization profiles are explored. Understanding the molecular basis of the interactions has lead to the recognition of the lipophobic effects. These nonspecific effects include those that arise from membrane perturbations and lipid chain packing and have been shown to modulate the energetics as well as the structural characteristics of membrane protein dimerization. In addition, specific interactions arising from direct protein–lipid interactions and protein–cholesterol interactions have been suggested to influence membrane protein association. We summarize here a few examples highlighting the role of the lipid bilayer on membrane protein organization.

Estimating the lipophobic contributions in model membranes - Dubey, Vikas; Prasanna, Xavier; Sengupta, Durba (Journal of Physical Chemistry B, 2017)
The insertion and association of membrane proteins is critical in several cellular processes. These processes were thought to be protein-driven, but increasing evidence points toward an important role of the lipid bilayer. The lipid-mediated contribution has been shown to be important in the association of membrane peptides, but the corresponding ``lipophobic'' component has not been directly estimated. Here, we calculate the free energy of insertion for transmembrane peptides and estimate the lipophobic component from the cost of cavity formation. The free-energy calculations were performed using the coarse-grain Martini force field, which has been successful in predicting membrane protein interactions. As expected, the charged moieties have the least favorable free energy of insertion and the highest cost of cavity formation. A length dependence was observed in polyalanine peptides with the lipid-mediated component increasing nonlinearly with peptide length. Membrane fluidity was tested by varying the temperature, and opposing effects were observed for short and long peptides. The dependence of the lipid-mediated effects on peptide length and temperature was not uniform and gives valuable insight into the anisotropic nature of the membrane. The results are an important step in estimating membrane effects in protein insertion and association.

Exploring GPCR lipid interactions by molecular dynamics simulations: excitements, challenges, and the way forward - Sengupta, Durba; Prasanna, Xavier; Mohole, Madhura; Chattopadhyay, Amitabha (Journal of Physical Chemistry B, 2018)
Gprotein-coupled receptors (GPCRs) are seven transmembrane receptors that mediate a large number of cellular responses and are important drug targets. One of the current challenges in GPCR biology is to analyze the molecular signatures of receptor-lipid interactions and their subsequent effects on GPCR structure, organization, and function. Molecular dynamics simulation studies have been successful in predicting molecular determinants of receptor-lipid interactions. In particular, predicted cholesterol interaction sites appear to correspond well with experimentally determined binding sites and estimated time scales of association. In spite of several success stories, the methodologies in molecular dynamics simulations are still emerging. In this Feature Article, we provide a comprehensive overview of coarse-grain and atomistic molecular dynamics simulations of GPCR-lipid interaction in the context of experimental observations. In addition, we discuss the effect of secondary and tertiary structural constraints in coarse-grain simulations in the context of functional dynamics and structural plasticity of GPCRs. We envision that this comprehensive overview will help resolve differences in computational studies and provide a way forward.